2003
DOI: 10.1074/jbc.m212788200
|View full text |Cite
|
Sign up to set email alerts
|

A Potassium Channel-MiRP Complex Controls Neurosensory Function in Caenorhabditis elegans

Abstract: MinK-related peptides (MiRPs) are single transmembrane proteins that associate with mammalian voltagegated K ؉ subunits. Here we report the cloning and functional characterization of a MiRP ␤-subunit, MPS-1, and of a voltage-gated pore-forming potassium subunit, KVS-1, from the nematode Caenorhabditis elegans. mps-1 is expressed in chemosensory and mechanosensory neurons and co-localizes with kvs-1 in a subset of these. Inactivation of either mps-1 or kvs-1 by RNA interference (RNAi) causes partially overlappi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
82
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 66 publications
(90 citation statements)
references
References 33 publications
8
82
0
Order By: Relevance
“…To strengthen the notion that the two proteins assemble in the pharynx we assessed the effect that epigenetic inactivation of mps-4 by RNAi had on the expression of EXP-2 tagged by GFP. Generally, KCNE proteins are essential components of their respective complexes that become unstable and/or cannot traffic to the plasma membrane without them (22,31). As expected, mps-4 RNAi selectively attenuated GFP signals in isthmus and terminal bulb (Fig.…”
Section: Mps-4 and Exp-2 Co-assemble In Pharyngeal Muscle-the Findingmentioning
confidence: 75%
See 2 more Smart Citations
“…To strengthen the notion that the two proteins assemble in the pharynx we assessed the effect that epigenetic inactivation of mps-4 by RNAi had on the expression of EXP-2 tagged by GFP. Generally, KCNE proteins are essential components of their respective complexes that become unstable and/or cannot traffic to the plasma membrane without them (22,31). As expected, mps-4 RNAi selectively attenuated GFP signals in isthmus and terminal bulb (Fig.…”
Section: Mps-4 and Exp-2 Co-assemble In Pharyngeal Muscle-the Findingmentioning
confidence: 75%
“…This disease predisposes to polymorphic tachyarrhythmias, and life threatening ventricular fibrillation (19). An important feature of kcne genes is that they are conserved across phyla (21)(22)(23). There are four kcne-related genes in Caenorhabditis elegans termed mps genes that play a prominent role in the nervous system of the animal.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…One of these transmembrane domain motif (S4) contains the positive charges responsible for sensing voltage. KVS-1 channels were cloned previously and expressed in a heterologous expression system and shown to have activation and inactivation kinetics resembling potassium channels of the Shal (Kv4) family (Bianchi et al 2003). However, a National Center for Biotechnology Information Blast comparison of the amino acid sequence of the KVS-1 ␣ subunit with the ␣ subunits of all 10 families of voltagedependent potassium channels showed that the KVS-1 channel was most similar in sequence to the Shab (Kv2) family.…”
Section: Resultsmentioning
confidence: 99%
“…We now report the reverse phenomenon, which we term "cumulative activation" (CA). In the KVS-1 channel, cloned from Caenorhabditis elegans (Bianchi et al, 2003), we observe a progressive frequency-dependent increase in outward current amplitude in response to repetitive depolarization. Thus, when two depolarizing pulses are repeated with an interpulse interval as long as 20 s, the peak outward current evoked by the second pulse is greater than the peak current of the preceding pulse.…”
Section: Introductionmentioning
confidence: 99%